Longitudinal profiling of the vaccination coverage in Brazil reveals a recent change in the patterns hallmarked by differential reduction across regions. (September 2020) - Césare, Náthaly; Mota, Tiago F.; Lopes, Fernanda F.L.; Lima, Ana Claudia M.; Luzardo, Ricardo; Quintanilha, Luiz Fernando; Andrade, Bruno B.; Queiroz, Artur T.L.; Fukutani, Kiyoshi F.
Highlights: There has been a recent reduction in vaccination coverage across the Brazilian regions. The most relevant reduction in vaccination coverage has occurred in childhood immunization. Increased web searches for anti-vaccine material has been associated with the reduction in immunization coverage. Abstract: Objective: Vaccination coverage is decreasing worldwide, favoring the potential reemergence of vaccine-preventable diseases. In this study, we performed a longitudinal characterization of vaccination coverage in Brazil and compared the profiles between the distinct regions in the country to test whether there has been a substantial change over the last 5 years. Methods: De-identified publicly available data were retrieved from the repository of the Brazilian Ministry of Health, comprising detailed information on vaccination coverage in all age groups between 1994 and 2019. The vaccination coverage for the whole country and for each Brazilian region, by year, was examined, and a time-series pattern analysis was performed. Results: A significant decrease in overall vaccination coverage across the country regions was observed between 2017 and 2019, especially in childhood immunization. A reduction in BCG, hepatitis B, influenza, and rotavirus vaccine coverage was observed. Conversely, vaccines against measles, mumps, rubella, varicella, and meningococcus showed an increase in coverage. Region-specific changes in vaccination patterns within the study period were observed. Conclusions: A substantial reduction in vaccination coverage was detected in Brazil, a country already highly susceptible to the emergence of epidemic infectious diseases. Continuing evaluation of the immunization program actions may help to improve vaccination coverage and prevent new epidemics.